Then they came for the dogs! - Hallsworth, Simon (Crime, law and social change, 2011)
This paper examines the British state’s desire to liquidate the Pit Bull as a breed. It examines the moral panic that brought the Pit Bull Terrier to public attention and traces the government’s knee-jerk response that resulted in the Dangerous Dogs Act (1991), the legal instrument that mandated Britain’s first attempt at canine genocide. Though public protection was the stated justification of this exercise in state violence, there was and is no evidence to support the case for canine killing through the indiscriminate blanket medium of breed specific legislation. Far from conceiving the dog an aggressor and humans its victims, this paper precedes on the assumption that the dogs are the victims and humans the inhuman aggressor. The paper concludes by examining the factors that provoked the UK’s descent into mass dog killing.